Carbon nanotubes oxidized by a green method as efficient metal-free catalysts for nitroarene reduction. Issue 3 (4th December 2014) - Wu, Shuchang; Wen, Guodong; Schlögl, Robert; Su, Dang Sheng
Abstract : Hydrogen peroxide (H2 O2 ) functionalized CNTs exhibited better catalytic performance than nitric acid (HNO3 ) oxidized samples in the reduction of nitroarenes. Abstract : Hydrogen peroxide (H2 O2 ) functionalized carbon nanotubes exhibited better catalytic performance than their nitric acid oxidized counterparts in the reduction of nitrobenzene. One important reason may be attributed to the notably less negative oxygenated groups on the surface of the former one.